Martyrdom in Early Victorian Scotland: Disruption Fathers and the Making of the Free Church - Brown, Stewart J. (Studies in church history, 1993)
‘Where is the Church of Scotland to be found?’ asked the leading Evangelical R. S. Candlish on 20 May 1843 at the first General Assembly of the Free Church of Scotland. ‘She will not be found basking under the smiles of the great, but she is to be recognised once more, as in days of old, by her sufferings and her tears.’ In 1843 the Disruption of the Church of Scotland brought the birth of a new church, the Free Church of Scotland, as nearly a third of the ministers and nearly half the lay membership left the national Church of Scotland. They went out in part over a long-standing dispute concerning church patronage, but, more fundamentally, they left in protest against what they perceived as the refusal of the State to recognize the Church’s independence in spiritual matters. The new Free Church claimed to be not merely a secession or schism, but rather the true national Church of Scotland, a claim its adherents based on their willingness to suffer for the principle of the headship of Christ in the Church. They were the Church of the martyrs of the Scottish Reformation and of the Covenants, willing to lay down their fortunes, even their lives, for ‘the Crown rights of the Redeemer’. The true Church of Scotland, asserted the Free Church minister James Mackenzie, in 1859, ‘began in 1843, when die old Church, the Church of Knox, of Melville, of Henderson, and of the martyrs, left its connexion with the State, and stood out before the world free, bearing the banner which our brave fathers bore.’